2009
DOI: 10.1111/j.1541-4337.2009.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives for Efficient and Sustainable Production of Surimi: A Review

Abstract: ABSTRACT:The links between fish processing and negative environmental impact need to be minimized. The overexploitation of white fish stocks has compromised supply, the use of energy contributes to a high-carbon footprint, and the water resources required are also high. An option is to resort to the use of alternative species and fisheries by-catch, together with the maximum utilization of fish. In addition, edible proteins from a range of sources could be converted into added-value products using surimi-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 175 publications
1
67
0
6
Order By: Relevance
“…Martin-Sanchez et al [23] reported that additives such as calcium compounds, chitosan and oxidizing agents seem to act by forming stronger protein gel networks [23].…”
Section: Texture Profile Analysis (Tpa)mentioning
confidence: 99%
“…Martin-Sanchez et al [23] reported that additives such as calcium compounds, chitosan and oxidizing agents seem to act by forming stronger protein gel networks [23].…”
Section: Texture Profile Analysis (Tpa)mentioning
confidence: 99%
“…Fish meat gel processing must regulate these phenomena. Various food additives to fish meat gel affect these phenomena (Martin-Sánchez et al, 2009;Yamashita et al 1999). Therefore, further studies are in progress to confirm the effect of rice flour on setting and modori of fish meat gel using the optimum rice flour.…”
Section: Discussionmentioning
confidence: 99%
“…Setting (Suwari) phenomenon of fish meat leads to an increase in the textural strength and elasticity of heat-induced gel preheated below 40℃ (Martin-Sánchez et al, 2009) In contrast, modori is a gel-weakening phenomenon of fish meat at around 50℃ _ 60℃…”
Section: Discussionmentioning
confidence: 99%
“…Surimi is made from minced fish flesh, providing opportunities to use underutilized species with little or no commercial value, fish too small to undergo a processing method or residues from the industrialization (Martín-Sánchez et al, 2009;Barreto & Beirão, 1999), so obtaining a value-added product despite of minimizing wastes and reducing environmental impacts.…”
Section: Introductionmentioning
confidence: 99%